Fecal Microbial Transplant in Individuals With Immune-Mediated Dry Eye - Watane, Arjun; Cavuoto, Kara M.; Rojas, Mario; Dermer, Harrison; Day, Joanne O; Banerjee, Santanu; Galor, Anat (American journal of ophthalmology, 2022)
Purpose: To evaluate the safety of the Fecal Microbial Transplant for Sjogren Syndrome (FMT) trial in individuals with immune-mediated dry eye (DE). Design: Open-label, nonrandomized clinical trial. Methods: The study population included 10 individuals with DE symptoms and signs meeting criteria for Sjögren or positive early Sjögren markers. Procedures were 2 FMTs from a single healthy donor delivered via enema, 1 week apart. The primary outcome measure was safety. In addition, gut microbiome profiles, DE metrics, and T-cell profiles in blood were examined at baseline before FMT, and at 1 week, 1 month, and 3 months after FMT. Results: The mean age of the population was 60.4 years; 30% were male; 50% were white; and 50% were Hispanic. At baseline, all subjects had significantly different gut microbiome profiles from the donor, including higher mean diversity indices. Subjects had a decreased abundance of genera Faecalibacterium, Prevotella, and Ruminococcus and an increased abundance of genera Alistipes, Streptococcus, and Blautia compared to the donor. Effector and regulatory T-cell profiles were positively correlated with each other and with DE symptom severity (T helper 1 cells [Th1]; r = .76; P = .01; Th17: r = 0.83; P = .003; CD25: r = 0.66; P = .04; FoxP3: r = 0.68; P = .03). No adverse events were noted with FMT. After FMT, gut microbiome profiles in 8 subjects moved closer to the donor's profile. As a group, gut microbiome profiles at all follow-up time points were more similar to the original recipients’ than the donor's microbiome; however, certain phyla, classes, and genera operational taxonomic unit (OTU) numbers remained closer to the donor vs recipients’ baseline profiles out to 3 months. Five individuals subjectively reported improved dry eye symptoms 3 months after FMT. Conclusions: FMT was safely performed in individuals with immune-mediated DE, with certain bacterial profiles resembling the donor out to 3 months after FMT. One-half the subjects reported improved DE symptoms. The most effective FMT administration method has yet to be determined.